2016
DOI: 10.1080/00222895.2016.1191416
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sensory Deficit on Phalanx Force Deviation During Power Grip Post Stroke

Abstract: The effect of sensory deficits on power grip force from individual phalanges was examined. We found that stroke survivors with sensory deficits (determined by the Semmes-Weinstein monofilament test) gripped with phalanx force directed more tangential to the object surface, than those without, although both groups had similar motor deficits (Chedoke-McMaster and Fugl-Meyer), grip strength, and skin friction. Altered grip force direction elevates risk of finger slippage against the object thus grip loss/object d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Augurelle et al (2003) reported that 7/10 participants dropped an object during anaesthesia of the fingerpads, while none would normally drop it. Power grip of larger objects is less affected (but see Enders and Seo 2017). Based on such work (see also Shibata and Santello 2017), one might expect that the range and variation of multi-digit hand postures would be altered after the loss of haptic feedback.…”
Section: Introductionmentioning
confidence: 99%
“…Augurelle et al (2003) reported that 7/10 participants dropped an object during anaesthesia of the fingerpads, while none would normally drop it. Power grip of larger objects is less affected (but see Enders and Seo 2017). Based on such work (see also Shibata and Santello 2017), one might expect that the range and variation of multi-digit hand postures would be altered after the loss of haptic feedback.…”
Section: Introductionmentioning
confidence: 99%
“…As a feasible and optimum choice for clinical use, the SWME is a well-established test for improved sensitivity of quantitative sensory testing, and widely applied in the assessment of neuropathy in the hospitals [45,46]. The SWME has been used in previous studies to determine sensory dysfunction at least 6 months post stroke [47].The SWME is composed of a hierarchical set of twenty monofilaments (Touch Test Sensory Evaluators, Stoetling Co., Wood Dale, IL, USA) [48].The range of monofilaments can distinguish significant sensory thresholds, including normal sensation, diminished tactile sensation, decreased protective sensation, and loss of protective sensation [49]. The assessors will start each test with a stiffness of filament with the participants' eyes closed.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Current measurement points for sensory assessment are mainly selected in the areas of the hand and upper limb where the function is achieved, such as the thumb and the index finger. Patients with stroke have been shown to have different sensory thresholds among the five fingers on the affected side ( Enders and Seo, 2016 ). Suda et al (2021) suggested that the light touch sensations of the thumb and the index finger were similar.…”
Section: Introductionmentioning
confidence: 99%